YAHUDI DALAM SUDUT PANDANG FILOSOFIS STUDI AGAMA: KONTRA ZIONISME DAN KONTRIBUSI KELOMPOK NATUREI KARTA PADA KLAUSUL PERDAMAIAN - Roma Ulinnuha (Religi: Jurnal Studi Agama-agama, 2015)
Having reviewed what it became the sole significance in religious studies realm, it is more likely that the peaceful outcome serves as the most desirable intention. The peaceful basis for all seems promising in the midst of prolonged disputes that sometimes bor rowed its justification through religion and religiosity. In the context of Judaism, the article discusses Naturei Karta, one of  Jewish commu- nities, applying Ninian Smart’s philosophical-political dimensions in religious studies. There are two queries in this article, i.e. how does Naturei Karta com- munity develop the view on the concept of  Israel, the state and Jewish commu- nity and how is Naturei Karta entity seen from philosophical-political dimen- sion in religious studies? The study exemplifies that Naturei Karta, actually bear a potential alternative solution based on the inherent concept of  “any place and land in the world are for Jewish people”. The concept gives the alter native territorial implication toward the claim of  formal state of  Israel. It serves not only as a part of  solution on Israel-Palestine conflict, but also the issue of identity within various Jewish communities. Until recently, the notion of  peace among entities seems pivotal as the ultimate outcome of philosophical dimension found in various faiths and religions.